Pengembangan Buku Ajar dan Augmented Reality pada Konsep Sistem Eksresi di Sekolah Menengah Atas - Nurdiyanti Nurdiyanti; Khalifah Mustami; Alimuddin Ali (UNM Journal of Biological Education, 2017)
The research was a Research and Development (R&D). The development model was 4Ddevelopment model which consists of four activity stages, namely: 1) define, 2) design, 3)development, and 4) dissemination. The research aimed to produce a textbook and an AugmentedReality which are valid, practical, and effective. The assessment instruments consist of three items,namely 1) validity instrument in a form of validity assessment instrument of textbook andAugmented Reality, 2) practicality instrument in a form of teachers and students’ responsesquestioner on textbook and Augmented Reality, 3) effectiveness instrument in a form of students’learning outcome evaluation test. Based on the data analysis, the average validity of the textbookand Augmented Reality by two expert assessors was 4.24 (valid) and 4.3 (valid), respectively.Media practicality of the text book and Augmented Reality based on teachers’ responses was 4.4(high) and 4.1 (high), respectively. Media effectiveness score was 89% students reached thelearning completeness score. Based on the result of the research, it could be concluded thattextbook and augmented reality that were developed were valid, practical, and effective.